Lowering the Schottky Barrier Height by Graphene/Ag Electrodes for High‐Mobility MoS2 Field‐Effect Transistors. Issue 2 (9th November 2018) - Chee, Sang‐Soo; Seo, Dongpyo; Kim, Hanggyu; Jang, Hanbyeol; Lee, Seungmin; Moon, Seung Pil; Lee, Kyu Hyoung; Kim, Sung Wng; Choi, Hyunyong; Ham, Moon‐Ho
Abstract: 2D transition metal dichalcogenides (TMDCs) have emerged as promising candidates for post‐silicon nanoelectronics owing to their unique and outstanding semiconducting properties. However, contact engineering for these materials to create high‐performance devices while adapting for large‐area fabrication is still in its nascent stages. In this study, graphene/Ag contacts are introduced into MoS2 devices, for which a graphene film synthesized by chemical vapor deposition (CVD) is inserted between a CVD‐grown MoS2 film and a Ag electrode as an interfacial layer. The MoS2 field‐effect transistors with graphene/Ag contacts show improved electrical and photoelectrical properties, achieving a field‐effect mobility of 35 cm 2 V −1 s −1, an on/off current ratio of 4 × 10 8, and a photoresponsivity of 2160 A W −1, compared to those of devices with conventional Ti/Au contacts. These improvements are attributed to the low work function of Ag and the tunability of graphene Fermi level; the n‐doping of Ag in graphene decreases its Fermi level, thereby reducing the Schottky barrier height and contact resistance between the MoS2 and electrodes. This demonstration of contact interface engineering with CVD‐grown MoS2 and graphene is a key step toward the practical application of atomically thin TMDC‐based devices with low‐resistance contacts for high‐performance large‐area electronics and optoelectronics. Abstract : Contact resistance between the channel and electrodes in MoS2 devices is significantly reduced using a low work function metal (Ag) and graphene as an interfacial layer between the MoS2 and the Ag because the Schottky barrier height is lowered at the contacts. Using graphene/Ag contacts instead of Ti/Au improves the field‐effect mobility, on/off current ratio, and photoresponsivity of the devices.